2014
DOI: 10.4252/wjsc.v6.i3.305
|View full text |Cite
|
Sign up to set email alerts
|

Sox2, a key factor in the regulation of pluripotency and neural differentiation

Abstract: Sex determining region Y-box 2 (Sox2), a member of the SoxB1 transcription factor family, is an important transcriptional regulator in pluripotent stem cells (PSCs). Together with octamer-binding transcription factor 4 and Nanog, they co-operatively control gene expression in PSCs and maintain their pluripotency. Furthermore, Sox2 plays an essential role in somatic cell reprogramming, reversing the epigenetic configuration of differentiated cells back to a pluripotent embryonic state. In addition to its role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
243
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(265 citation statements)
references
References 52 publications
17
243
1
4
Order By: Relevance
“…Interestingly, while the expression of swine endogenous OCT4, KLF4 and NANOG was downregulated 4 days after doxycycline withdrawal, the expression of swine endogenous SOX2 and c-MYC appeared to be upregulated (Supplementary Fig. 5A), possibly due to the induction of early neuroectodermal/progenitor lineage that may maintain a high expression level of SOX2 and c-MYC[23, 24]. Notably, a marked reduction of all five swine endogenous pluripotency markers including SOX2 and c-MYC was observed upon a 12-day spontaneous differentiation of siPSCs in the absence of doxycycline and self-renewal growth factors (LIF and bFGF) (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, while the expression of swine endogenous OCT4, KLF4 and NANOG was downregulated 4 days after doxycycline withdrawal, the expression of swine endogenous SOX2 and c-MYC appeared to be upregulated (Supplementary Fig. 5A), possibly due to the induction of early neuroectodermal/progenitor lineage that may maintain a high expression level of SOX2 and c-MYC[23, 24]. Notably, a marked reduction of all five swine endogenous pluripotency markers including SOX2 and c-MYC was observed upon a 12-day spontaneous differentiation of siPSCs in the absence of doxycycline and self-renewal growth factors (LIF and bFGF) (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in this study, we also investigated the expression of pluripotent genes such as OCT4, Nanog and Sox2 because canine embryonic stem cells were demonstrated to express Oct4, Nanog, and Sox2 at high levels [38] . Sox2 governs ESC specification to neuroectoderm while Oct4 and Nanog promote their differentiation to mesendoderm, a common precursor of mesoderm and definitive endoderm [39] , and Sox2 is a critical factor for directing the differentiation of pluripotent stem cells to neural progenitors and for maintaining the properties of neural progenitor stem cells [40] . In this study, we observed expressions of these pluripotent genes in OS cells and detected the downregulation of Nanog, Oct4 and the upregulation of Sox2 ALTUNBAŞ, YAPRAKÇI ÇELİK in the NSs derived from OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, C44 is highly active in ESC and remains active at later stages in all 4 brain tissues, suggesting its critical role in the regulation of pluripotency and neural differentiation. Indeed, Sox2 from C44 has been demonstrated to be a pluripotency factor and play a pivotal role in neural differentiation 23 . Similar to C44, C6 also exhibits ectoderm-specific pattern from E10.5 to P0.…”
Section: Transcriptional Waves During Embryogenesismentioning
confidence: 99%